A new species of Pinguicula (Lentibulariaceae) from central America - Zamudio, Sergio (Instituto de Ecología, A.C., 1997)
Pinguicula mesophytica is described as a new species for the science. This plant has been confused with P. moranensis HBK., from which it differs in its smaller red corollas with suborbicular or oblate upper lobes and obovate lower lobes, in its petiolate leaves with ciliate petioles and in its epiphytic or rupicolous habit. These characters indicate a more direct relationship with P. cyclosecta Casper. The distribution area of the new species marks the southern limit of the section Orcheosanthus.